Use of low-value pediatric services in the Military Health System - Tracey Pérez Koehlmoos; Cathaleen Madsen; Amanda Banaag; Qiong Li; Andrew J. Schoenfeld; Joel S. Weissman (BMC, 2020)
Abstract Background Low-value care (LVC) is understudied in pediatric populations and in the Military Health System (MHS). This cross-sectional study applies previously developed measures of pediatric LVC diagnostic tests, procedures, and treatments to children receiving care within the direct and purchased care environments of the MHS. Methods We queried the MHS Data Repository (MDR) to identify children (n = 1,111,534) who received one or more of 20 previously described types of LVC in fiscal year 2015. We calculated the proportion of eligible children and all children who received the service at least once during fiscal year 2015. Among children eligible for each measure, we used logistic regressions to calculate the adjusted odds ratios (AOR) for receiving LVC at least once during fiscal year 2015 in direct versus purchased care. Results All 20 measures of pediatric LVC were found in the MDR. Of the 1,111,534 eligible children identified, 15.41% received at least one LVC service, and the two most common procedures were cough and cold medications in children under 6 years and acid blockers for infants with uncomplicated gastroesophageal reflux. Eighteen of the 20 measures of pediatric LVC were eligible for comparison across care environments: 6 were significantly more likely to be delivered in direct care and 10 were significantly more likely to be delivered in purchased care. The greatest differences between direct and purchased care were seen in respiratory syncytial virus testing in children with bronchiolitis (AOR = 21.01, 95% CI = 12.23-36.10) and blood tests in children with simple febrile seizure (AOR = 24.44, 95% CI = 5.49-108.82). A notably greater difference of inappropriate antibiotic prescribing was seen in purchased versus direct care. Conclusions Significant differences existed between provision of LVC services in direct and purchased care, unlike previous studies showing little difference between publicly and privately insured children. In fiscal year 2015, 1 in 7 children received one of 20 types of LVC. These proportions are higher than prior estimates from privately and publicly insured children, suggesting the particular need to focus on decreasing wasteful care in the MHS. Collectively, these studies demonstrate the high prevalence of LVC in children and the necessity of reducing potentially harmful care in this vulnerable population.